ANALISIS SEKTOR UNGGULAN DALAM STRUKTUR PEREKONOMIAN KABUPATEN LAMONGAN - MOCH. ARIF PURNOMO (Universitas Negeri Surabaya, 2013)
The purpose of this research is to identify sectors that became the base sector as a leading sector in Lamongan, analyze the performance growth especially the leading sector, and analyze the impact of income multiplier of the base sector. The research method used is descriptive quantitative research methods. While analysis tools used in the research is the Location Quotient (LQ), Shift Share analysis, and the Multiplier effect. Research results show that during the research of 2007-2011, based on the results of the analysis of the Location Quotient which is the base sector as a leading sector in Lamongan is the agricultural sector. Based on the results of the Shift Share analysis showed that the agricultural sector experienced a slower growth but have the competitiveness regions compared with the similar sectors in west java. While based on the Multiplier Effect analysis showed fluctuate value. Keywords: Sector Base, Location Quotient, Shift Share, Multiplier effect.